GHAFUR GHULAM IS A PERSON WHO HAS A STRONG STRENGTH - Gulomjonov Hakimbek (Web of Journals Publishing, 2024)
Ghafur Ghulam's hardships, his hard work and their results before reaching the level of a writer, his desire to learn even in difficult times.
Keywords: troubled childhood, difficult lifestyle, hard work, passion, poet, works.